PENGARUH STABILITAS KEUANGAN, TARGET KEUANGAN, KETIDAKEFEKTIFAN PENGAWASAN, PERGANTIAN AUDITOR DAN KOLUSI TERHADAP KECURANGAN LAPORAN KEUANGAN : THE EFFECT OF FINANCIAL STABILITY, FINANCIAL TARGETS, SUPERVISORY INEFECTIVENESS, AUDITOR CHANGE AND COLLUSION ON FINANCIAL STATEMENT FRAUD - Ivonita, Azzahra; Rasuli, M; Wiguna, Meilda (Universitas Riau, 2024)
This study examines the effect of financial stability, financial targets, ineffective monitoring, auditor switching and collusion on fraudulent financial statements. The population of this study are state-owned companies listed on the IDX for 2018-2021. The research sample was selected using purposive sampling method. With a total of 60 observations of annual financial reports. The type of data used is secondary data, which is in the form of annual reports of companies listed on the IDX during the 2018-2021 period. Hypothesis testing was carried out using multiple linear regression methods using SPSS17 software. The results of the study show that financial targets, Ineffective monitoring, auditor turnover and collusion have proven to have an effect on fraudulent financial reporting. Meanwhile, financial stability has no effect on financial statements.